Determinants of health-related quality of life decline in interstitial lung disease - Maqhuzu, Phillen Nozibuyiso; Szentes, Boglarka L.; Kreuter, Michael; Bahmer, Thomas; Kahn, Nicolas; Claussen, Martin; Holle, Rolf; Schwarzkopf, Larissa (Health and quality of life outcomes, 2020)
Background: Health-related quality of life (HRQL) in interstitial lung disease (ILD) patients is impaired. We aimed to identify baseline predictors for HRQL decline within a 12-month observation period. Methods: We analyzed 194 ILD patients from two German ILD-centers in the observational HILDA study. We employed the disease-specific King’s Brief Interstitial Lung Disease questionnaire (K-BILD) with the subdomains ‘psychological impact’, ‘chest symptoms’ and ‘breathlessness and activities’, and the generic EQ-5D Visual Analog Scale (VAS). We evaluated how many patients experienced a clinically meaningful decline in HRQL. Subsequently, we investigated medical and sociodemographic factors as potential predictors of HRQL deterioration. Results: Within the study population (34.0% male, Ø age 61.7) mean HRQL scores hardly changed between baseline and follow up (K-BILD: 52.8 vs. 52.5 | VAS: 60.0 vs. 57.3). On the intra-individual level, 30.4% (n = 59) experienced a clinically relevant deterioration in K-BILD total score and 35.4% (n = 68) in VAS. Lower baseline forced vital capacity (FVC) % predicted determined HRQL decline in K-BILD total score (ß-coefficient: − 0.02, p = 0.007), VAS (ß-coefficient: − 0.03, p < 0.0001), and in the subdomain ‘psychological impact’ (ß-coefficient: − 0.02, p = 0.014). Lower baseline diffusing capacity of carbon monoxide (DLCO) % predicted determined deterioration in ‘breathlessness and activities’ (ß-coefficient: − 0.04, p = 0.003) and ‘chest symptoms’ (ß-coefficient: − 0.04, p = 0.002). Additionally, increasing age predicted decline in ‘psychological impact’ (ß-coefficient: 0.06, p < 0.007). Conclusion: Around a third of ILD patients experienced a clinically relevant HRQL deterioration in a 12-month period, which was associated with baseline lung function values in all K-BILD domains. As lung function values are time-dependent variables with possible improvements, in contrast to age and ILD subtype, it, thus, seems important to improve lung function and prevent its decline in order to maintain HRQL on the possibly highest level.